Nudt7 gene depletion causes transcriptomic change in early development of zebrafish. (21st October 2022) - Bhandari, Sushil; Hong, KwangHeum; Miyawaki-Kuwakado, Atsuko; Tomimatsu, Kosuke; Kim, Yong-Il; Nam, In-Koo; Sagerström, Charles G; Nakamura, Mako; Choe, Seong-Kyu
Abstract: The Nudt family has been identified as enzymes performing Coenzyme A to 3′5′-ADP + 4′-phospho pantetheine catalysis. The members of this family have been shown to be particularly involved in lipid metabolism, while their involvement in gene regulation through regulating transcription or mRNA metabolism has also been suggested. Here, we focused on peroxisomal NUDT7, possessing enzymatic activity similar to that of its paralog, peroxisomal NUDT19, which is involved in mRNA degradation. No reports have been published about the Nudt family in zebrafish. Our transcriptomic data showed that the Nudt family members are highly expressed around zygotic gene activation (ZGA) in developing zebrafish embryos. Therefore, we confirmed the computational prediction that the products of the nudt7 gene in zebrafish were localized in the peroxisome and highly expressed in early embryogenesis. The depletion of nudt7 genes by the CRISPR/Cas9 system did not affect development; however, it decreased the rate of transcription in ZGA. In addition, H3K27ac ChIP-seq analysis demonstrated that this decrease in transcription was correlated with the genome-wide decrease of H3K27ac level. This study suggests that peroxisomal Nudt7 functions in regulating transcription in ZGA via formation of the H3K27ac domain in active chromatin. Graphical Abstract: